Upaya meningkatkan hasil belajar siswa dalam mengerjakan soal cerita pada mata pelajaran matematika melalui metode bermain kartu soal pada siswa kelas VI sekolah dasar - Eva Khuzaimah (Jurnal Pendidikan Dasar, 2020)
Abstract. Classroom action research aims descriptively to find out the influence of the method of playing card questions on improving the ability to work on story problems in mathematics class VI in  SD Negeri 1 in the 2017/ 2018 academic year. Subjects given the action are grade VI in SD Negeri 1 in the 2017/2018 academic year of 26 students and divided into 6 groups. The results of the study descriptively showed that the tendency of mathematics learning outcomes for Grade VI students of SD Negeri 1 Padaan was an increase, namely with the acquisition of an average score before the action was held at 59.69 and after the action was taken to be 66.5 thus meaning there was an increase in achievement by 6 , 81.Kata kunci: learning outcomes, question cards, story problems, elementary school